The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1038/s41598-017-08557-y
|View full text |Cite
|
Sign up to set email alerts
|

Fault reactivation and earthquakes with magnitudes of up to Mw4.7 induced by shale-gas hydraulic fracturing in Sichuan Basin, China

Abstract: This paper presents a timely and detailed study of significant injection-induced seismicity recently observed in the Sichuan Basin, China, where shale-gas hydraulic fracturing has been initiated and the aggressive production of shale gas is planned for the coming years. Multiple lines of evidence, including an epidemic-type aftershock sequence model, relocated hypocenters, the mechanisms of 13 large events (M W > 3.5), and numerically calculated Coulomb failure stress results, convincingly suggest that a serie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
196
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 197 publications
(203 citation statements)
references
References 48 publications
6
196
1
Order By: Relevance
“…[26][27][28][29] Engineering monitoring in this study proved this point, the maximal moment magnitude Some scholars pointed out that West Canadian reservoirs and Sichuan Basin in China experienced anomalous activity during multistage fracturing, the microseismic moment magnitude was more than 4.…”
Section: Slippingsupporting
confidence: 67%
“…[26][27][28][29] Engineering monitoring in this study proved this point, the maximal moment magnitude Some scholars pointed out that West Canadian reservoirs and Sichuan Basin in China experienced anomalous activity during multistage fracturing, the microseismic moment magnitude was more than 4.…”
Section: Slippingsupporting
confidence: 67%
“…Previous studies have reported some shallow earthquakes in the southern Sichuan Basin in the vicinity of the oil and gas wells, mostly triggered by hydraulic fracturing (e.g., Lei et al, 2008Lei et al, , 2017. However, the closest oil and gas wells with associated induced seismicity are located at least 40 km away from the Dianjiang earthquake.…”
Section: Discussionmentioning
confidence: 99%
“…The basement faults are hidden in the crystal basement (>5 km) and show minor activity . Based on the Chongqing Seismic Network catalog (1990 to 2018), there was no other M > 3.5 event within 100 km of the Dianjiang earthquake, indicating a low background seismic rate, although many shallow earthquakes in the Sichuan Basin have been linked with wastewater injection (e.g., Lei et al, 2008) and hydraulic fracturing in shale gas fields (e.g., Lei et al, 2017;Figure 1a). Based on the Chongqing Seismic Network catalog (1990 to 2018), there was no other M > 3.5 event within 100 km of the Dianjiang earthquake, indicating a low background seismic rate, although many shallow earthquakes in the Sichuan Basin have been linked with wastewater injection (e.g., Lei et al, 2008) and hydraulic fracturing in shale gas fields (e.g., Lei et al, 2017;Figure 1a).…”
Section: Introductionmentioning
confidence: 99%
“…Individual case examples of HF‐induced seismicity have been now be identified in Alberta (e.g., Wang et al, ), Arkansas (Yoon et al, ), British Columbia (e.g., B.C. Oil and Gas Commission, ), California (Kanamori & Hauksson, ), China (e.g., Lei et al, ), England (Clarke et al, ), Ohio (e.g., Skoumal et al, ), Oklahoma (e.g., Holland, ), Pennsylvania (Skoumal et al, ), and West Virginia (Skoumal et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…This interpretation was based on the few documented cases of HF‐induced seismicity, with the cases consistent of small‐magnitude events. Since these interpretations were made, larger‐magnitude earthquakes that have been attributed to hydraulic fracturing have occurred, including the 2015 M 4.6 earthquake in British Columbia, Canada (Atkinson et al, ; Mahani et al, ), and the 2016 M 4.7 earthquake in the Sichuan Basin, China (Lei et al, ). Additionally, while the number of cases identified prior to these studies was limited (Clarke et al, ; Darold et al, ; Friberg et al, ; Holland, ), more recent studies have found a higher prevalence of HF‐induced seismicity than would have been previously expected (Atkinson et al, ; Skoumal et al, ).…”
Section: Introductionmentioning
confidence: 99%